2017
DOI: 10.1111/1750-3841.13593
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition Analysis, Sensory, and Feasibility Study of Tree Peony Seed

Abstract: Eight wild species in Sect. Moutan DC (tree peony) of the genus Paeonia grown in natural habitats and 1 cultivated specie were investigated to analyze their fatty acid and bioactive phenolic compound profiles. For fatty acid composition, P. ludlowii contained the lowest α-linolenic acid (27.68%) and P. jishanensis contained the highest (51.96 %) content of the 9 species. For phenolic compounds, P. qiui contained the highest resveratrol (2.12 mg/g), P. delavayi contained the highest β-gentiobiosylpaeoniflorin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…We detected nine fatty acids, with various FAs in seeds showing different concentrations ( Table 2). The FA compositions were similar to those in tree peonies reported by Mao et al [20] The Table 1. Phenotypic characteristics of the seeds from 14 populations (mean � SD, n = 3).…”
Section: Fatty Acid Compositionsupporting
confidence: 86%
“…We detected nine fatty acids, with various FAs in seeds showing different concentrations ( Table 2). The FA compositions were similar to those in tree peonies reported by Mao et al [20] The Table 1. Phenotypic characteristics of the seeds from 14 populations (mean � SD, n = 3).…”
Section: Fatty Acid Compositionsupporting
confidence: 86%
“…The five major fatty acids all remained essentially unchanged (p ≥ 0.05) with the three major unsaturated acids accounting for more than 90% of the total fatty acids composition, which agrees with previous work with unroasted peony seeds oil. [7] Similarly, the fatty acids compositions of safflower oils were not significantly affected by roasting temperatures. [26] TPSO with its high level of α-linolenic acid, which is an essential fatty acid, may allow it to be marketed as a nutraceutical.…”
Section: Resultsmentioning
confidence: 94%
“…Mao, et al found paeoniflorin had a concentration of 23.7 mg/g in tree peony seeds. [7] Another possibility is aquathermolysis of benzaldehyde to benzoic acid. [35] Further study needs to be done to determine the formation of benzoic acid in roasted TPSO.…”
Section: Determination Of Benzoic Acid In Tpsomentioning
confidence: 99%
See 1 more Smart Citation
“…is native to China and has a high ornamental, medicinal, and economic value. Tree peony is also known as the 'king of flowers', and its seeds have the high oil value (Mao et al 2017, Han et al 2018). In addition, the root bark of tree peony is used in traditional Chinese medicine, and paeonol and paeoniflorin are important components for the treatment of breast cancer and neuropathic pain (Shah et al 2018).…”
Section: Introductionmentioning
confidence: 99%